2020
DOI: 10.3390/ijerph17114180
|View full text |Cite
|
Sign up to set email alerts
|

A WHO Pathfinder Survey of Dental Caries in 6 and 12-Year Old Transylvanian Children and the Possible Correlation with Their Family Background, Oral-Health Behavior, and the Intake of Sweets

Abstract: To our knowledge, recent oral health data in Romania is poor, as no comprehensive oral health surveys have been carried out in the last five years. The present cross-sectional oral health survey aimed to assess the dental health status in 6 and 12-year old children from Transylvania, in correlation with their family background, oral-health behavior, and the intake of sweets. The study was conducted on 290 children from nine schools in the Transylvanian region of Romania. The study consisted of the clinical exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
(19 reference statements)
2
2
0
Order By: Relevance
“…Our study is the most significant done during the last ten years in our country, analyzing a large people group that investigates the dental caries prevalence and the pro cariogenic food intake. Previous studies on the youth age range published similar statistics on 290 subjects, consisting of children and teenagers of different ages (Lucaciu, IJESPH 2020) [40], and 592 teenagers (Baciu, 2015) [14]. Together with nutritional behaviors, our study revealed the still low attendance of dental and medical check-ups in adolescents in our country, with significant consequences in the caries prevalence.…”
Section: Strengthssupporting
confidence: 71%
“…Our study is the most significant done during the last ten years in our country, analyzing a large people group that investigates the dental caries prevalence and the pro cariogenic food intake. Previous studies on the youth age range published similar statistics on 290 subjects, consisting of children and teenagers of different ages (Lucaciu, IJESPH 2020) [40], and 592 teenagers (Baciu, 2015) [14]. Together with nutritional behaviors, our study revealed the still low attendance of dental and medical check-ups in adolescents in our country, with significant consequences in the caries prevalence.…”
Section: Strengthssupporting
confidence: 71%
“…The current study demonstrated that subjects with SOS teeth are more likely to be residents of rural versus urban, and within urban in Jewish more than in non-Jewish localities. Supporting our results, a recent WHO survey demonstrated that carious lesions are left without treatment mostly in rural areas [ 32 ]. Perinetti et al demonstrated that caries prevalence in the primary and the permanent dentition of school children living in rural areas is significantly higher than that of children living in urban areas, suggesting that in older subjects the urbanization level may become a strong indicator for dental caries [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to the findings of the present study, the D component was the major part of the DMFT index in 12-year-old Bosnian children. That was also the finding from the pathfinder survey in the neighboring Romania, especially in children from rural areas [36].…”
Section: Discussionsupporting
confidence: 63%